2011
DOI: 10.3892/ijo.2011.1150
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for cardiac atrophic remodeling in cancer-induced cachexia in mice

Abstract: Abstract. Cachexia is a common complication in cancer patients, which dramatically reduces quality of life and survival. In contrast to the well-studied feature of skeletal muscle loss, alterations in cardiac muscle are unclear. Recently, we reported that heart contractile function was significantly impaired in mice with colon-26 (C26) tumors, a widely used rodent model of cancer cachexia. In the present study, we investigated the potential underlying mechanisms for decreased heart function, specifically relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 0 publications
5
42
0
Order By: Relevance
“…Cancer cachexia, a syndrome consisting of fatigue, muscle wasting, and weight loss with or without anorexia, is observed in a large percentage of cancer patients with incurable disease [1] and contributes to 22 percent of cancer deaths [1, 2]. New research by our lab and others has shown that cancer cachexia involves not only the loss of skeletal muscle, but can also cause pathologic alterations within the heart [2, 3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cancer cachexia, a syndrome consisting of fatigue, muscle wasting, and weight loss with or without anorexia, is observed in a large percentage of cancer patients with incurable disease [1] and contributes to 22 percent of cancer deaths [1, 2]. New research by our lab and others has shown that cancer cachexia involves not only the loss of skeletal muscle, but can also cause pathologic alterations within the heart [2, 3].…”
Section: Introductionmentioning
confidence: 99%
“…New research by our lab and others has shown that cancer cachexia involves not only the loss of skeletal muscle, but can also cause pathologic alterations within the heart [2, 3]. The resultant effects on myocardial function likely contribute to fatigue and decreased quality of life in these patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis of cardiac atrophy remains poorly explored but seems to share similar mechanisms with skeletal muscle atrophy. Indeed, reduced protein synthesis and increased protein degradation in hearts of cachectic rodents were detected [33,34]. In addition, cardiomyocytes apoptosis was also observed in AH-130 tumour-bearing rats and C26 tumour bearing mice cachectic models [35,36].…”
Section: Cancer Cachexiamentioning
confidence: 99%
“…Pathologic insults were demonstrated by showing that tumor-bearing mice presented with reduced levels of PPAR-α and carnitine palmitoyltransferase (CPT1β), compared to those without tumors (Tian et al, 2011). This phenomenon suggested that pathological hypertrophy occurs through the down regulation of fatty acid metabolism.…”
Section: Introductionmentioning
confidence: 99%